Antimicrobial, antioxidant and anticancer activity of Ephedra alata growing in East of Libya1 - Alshalmania, Salmin; Bengleilb, Mudafara; Elshibania, Fatma (Libyan Journal of Science &Technology, 2022)
Introduction: The plant Ephedra alata belongs to the Ephederiaceae family. These plants distributed in North Africa, Palestine, Libya, Egypt, Saudi Arabia, and Iraq. Ephedra alata has been commonly used in folk medicine in Libya and most of the Arabian countries for treatment of asthma, hay fever, and the common cold. Aim: This study aimed to investigate the phyto-constituents and to assess its anti-microbial, antioxidant activities, in addition, to study its cytotoxic effect. Methods: The aerial part dried of the plant was subjected to a phytochemical screening and investigated for their antimicrobial activity, antioxidant effect, and cytotoxic effects. Results: The phytochemical investigation of the methanolic extracts of Ephedra alata revealed the presence of alkaloids, carbohydrates, flavonoides, steroids, tannins, and phenolic compounds. The results of anti-microbial activity revealed that; there was a significant antibacterial activity against representatives of Gram positive (Staphylococcus aureus, Bacillus subtilis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa), while there was no antifungal effect against Aspergillusflavus and Candida albicans. In terms of antioxidant activity, the methanolic extract of Ephedra alata showed a significant scavenging effect on the DPPH radical, compared to gallic acid. The results showed an honest correlation between antioxidant activity and flavonoid content. The plant extract displayed a significant cytotoxic effect on MCF7with IC50 and IC90 comparing with doxorubicin as a positive control. Conclusion: The results indicated that the extract of Ephedra alata had significant antioxidant, and cytotoxic effects in addition to their antimicrobial activity